Attitudes of Catholic Clergies to the Application of ChatGPT in Unite Religious Communities - Ignatowski, Grzegorz (Religions, 2024)
The article “Attitudes of Catholic clergies to the application of ChatGPT in unite religious communities” investigates the perspectives of the Catholic clergy on the integration of ChatGPT technology in religious environments. Bearing in mind that communication technologies are becoming an integral part of every aspect of life, including religious practices, the study delves into the potential, advantages, and challenges associated with using ChatGPT to support religious discourse. Adopting a qualitative approach, in-depth interviews were conducted with eleven Polish priests, addressing the diversity within the group. The respondents, who play important roles in organising the life of Catholic religious communities, highlighted ChatGPT’s potential in enhancing the dissemination of information, educational initiatives, and pastoral care. However, they also expressed concerns about the technology’s impact on genuine human interactions and the preservation of religious practices.